Evaluation of the placental environment with a new in vitro model of histocultures of early and term placentae: determination of cytokine and chemokine expression profiles - Faye, Albert (2005)
We aimed to set up and validate a new in vitro model of placental histocultures, for the evaluation of cytokine and chemokine profiles of the placental environment, over a long culture period. Micro-explant cultures from 6 early and 6 term placentae were set up on collagen sponge gel supports at a liquid/air interface. At various times during culture, we analyzed tissue morphology and cell death by microscopy and quantified beta-hCG production and mRNA levels for beta-hCG and insulin-like 4 (INSL4). Levels of IL-6, LIF, TNF alpha, IL-10, IFN-gamma, IL-16 and RANTES in the medium were measured by ELISA on days 1, 4 and 7 of culture. SDF-1 mRNA expression was determined by real-time PCR at the same time points. Histocultures from early and term placentae remained viable until day 10. High levels of IL-6 and LIF production, low levels of TNF alpha, IL-10 and IFN-gamma production and significant SDF-1 expression were observed. These data indicate that placental histoculture is a suitable and reliable in vitro model for studying the placental environment.